FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELENGKAPAN IMUNISASI DASAR PADA BAYI PADA MASA PANDEMI COVID 19 - Rauda Rauda; Friska Halawa (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Immunization is a form of a health program that is very effective in reducing infant and under-five mortality. During the COVID-19 pandemic, immunization services as one of the essential health services remain a priority to be implemented. The basic immunizations are Hepatitis B, BCG, DPT, Polio, HB, and measles immunizations. Immunization can prevent the occurrence of a disease and can control the baby's growth rate. The purpose of this study was to determine the factors associated with the completeness of basic immunization in infants.The design of this research is an analytic survey with a cross-sectional approach. The sampling technique was the total population, which was 45 mothers. The results of this study are the majority of respondents have less knowledge as many as 26 people (44.9%). The majority of respondents do not work as many as 28 people (62.2%). The majority of respondents received family support, namely 27 people (60.0%). The majority of respondents were unreachable as many as 28 people (62.2%).The conclusions in this study are the relationship between knowledge, mother's occupation, family support, and distance from the place of service with the completeness of basic immunization in infants. Suggestions to health workers, especially midwives and Posyandu cadres in monitoring children's immunizations, especially during the COVID 19 pandemic. So that all children get routine immunizations on time without parents worrying about being exposed to the COVID 19 virus.Keywords: basic immunization, baby, covid 19